Pengaruh Ketahanan Pangan Terhadap Inflasi Khususnya Produk Cabai - Barnabas Jermias Jacob Salmoen Pella (Universitas Katolik Widya Karya Malang, 2024)
The purpose of this writing is to provide a real picture of community food security against inflation, in this case the chili plant. The research method used by the author is to use a survey method where the condition of chili prices in traditional markets is the object of study. Inflation is a situation where the purchasing power of a community The country experienced a decline because the country's currency exchange rate was declared to have decreased. This happened because of several things, one of which was because the prices of goods and services continued to increase because demand was higher than supply. If this is not anticipated, the country will experience a financial deficit because it has to balance price balance. Food sources are a need for every living creature, in this case food humans who have culture and tastes consume food according to tradition and culture. Chilli is one of the products. with a characteristic spicy taste that almost every human being is looking for in complementary food products, demand and supply greatly influence prices, certain product ingredients are needed by many people but the products are limited, so there will be an increase in prices. Problem: Can inflation be controlled with resilience? One of the food sources is the cultivation of chili products.